Influence of Mind Mapping in Counseling to Increase Students’ Creative Thinking - Irman Irman; Silvianetri Silvianetri (AL-ISHLAH: Jurnal Pendidikan, 2022)
The main problem experienced by students today is the low level of creative thinking. One treatment that can be used to improve students' creative thinking is mind mapping in counselling. This study aims to examine the influence of mind mapping in counselling to increase students' creative thinking. This research method uses true experiments with a pretest posttest control group design. The research population is the students of a public junior high school in Malang City. The research sample was 16 people who were taken randomly. The research instrument used a creative thinking test with a validity of 0.950, reliability of 0.943 and data analysis using an independent t-test. The results showed: (1) mind mapping is a very appropriate and interesting technique used in counselling services because the way mind mapping works is in accordance with the brain structure that makes students relax and happy, (2) there is a significant influence of mind mapping in counselling on improving students' creative thinking. This study has limitations in terms of the number of samples in the intervention is still small and tested in one school. It is recommended to be tested on a large sample in schools at various levels and cultures.